Provider-reported use of butylscopolamine in gastrointestinal endoscopy in Germany - Ullmann, Octavia; Ranti, Daniel; Georgiadou, Ekaterini; Hillemacher, Thomas; Schmidt, Arthur; von Hahn, Thomas (Endoscopy International Open, 2024)
Introduction The anti-cholinergic agent hyoscine-N-butylbromide (HBB) is used in gastrointestinal (GI) endoscopy to decrease motility and facilitate endoscopic procedures. Data from clinical studies to support this practice is limited especially for therapeutic procedures. Likewise, patterns of use among endoscopist are largely unclear. This study sought to assess usage of HBB among German-speaking endoscopists.Material and Methods We conducted an anonymous online survey among endoscopists in German-speaking countries.Results A total of 207 physicians participated in the survey. The majority (76.9%) were experienced endoscopists and 92.3% of respondents use HBB at least occasionally during procedures. The reported median stated frequency of HBB use varied greatly between different types of procedures and increased with the complexity of the procedure being performed. HBB was rarely used in diagnostic esophagogastroduodenoscopies (EGD) (median stated frequency 1% of procedures), while use frequency was significantly higher in EGD with endoscopic mucosal resection (EMR) (10%; p=0.002) and EGD with endoscopic submucosal dissection (ESD) (20%; p<0.001). Similarly, use frequency during diagnostic colonoscopy was lower (5%) compared to colonoscopy with EMR (20%, p=0.005) or ESD (42.5%, p<0.001). The highest use frequency was reported for ERCP (50%). The most frequently stated reason to use HBB was facilitation of the procedure (80.6%) followed by increasing diagnostic yield (58.3%).Conclusion German-speaking endoscopists commonly use HBB, most frequently to facilitate complex therapeutic procedures. Given there is almost no data supporting HBB use in therapeutic endoscopy, we suggest that more research is needed to evaluate benefits and risks of this practice.
Keywords: Quality and logistical aspects; Performance and complications; Diagnostic ERC